2014
DOI: 10.2298/jsc130112056a
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound and methanol for rapid removal of surfactant from MCM-41

Abstract: Ultrasound waves were successfully applied for the removal of the template from mesoporous MCM-41 molecular sieve. The method uses 28 KHz ultrasound irradiation in a methanol solvent for disrupting the micellar aggregation of the surfactant molecules, cetyltrimethylammonium bromide, which fill the pores of as-synthesized MCM-41. After 15 min sonication at the moderate temperature of 40 °C, the majority of surfactant molecules had been removed from powder MCM-41. The template removal rate using ultrasound irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Therefore, several studies have used microwave [15] or other irradiation [16] and supercritical [17] or refluxing solvents [18,19] to achieve complete extraction of templates and template recycling after elution. [20] Although there have been reports of complete template elutionw ithoutt he need for such promoters, these require that the materiali sd esigned to allow for elution through the choice of template molecule, and therefore compromise materials properties compared to their parent materials. [4,19] For example, hexagonal-mesoporous silica (HMS) uses Despite significant improvements in the synthesis of templated silica materials, post-synthesisp urification remains highly expensive and renders the materials industrially unviable.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have used microwave [15] or other irradiation [16] and supercritical [17] or refluxing solvents [18,19] to achieve complete extraction of templates and template recycling after elution. [20] Although there have been reports of complete template elutionw ithoutt he need for such promoters, these require that the materiali sd esigned to allow for elution through the choice of template molecule, and therefore compromise materials properties compared to their parent materials. [4,19] For example, hexagonal-mesoporous silica (HMS) uses Despite significant improvements in the synthesis of templated silica materials, post-synthesisp urification remains highly expensive and renders the materials industrially unviable.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 7(a)−(c), the spectra of all samples were similar, indicating that the structure of CTABr was preserved after sonication in ethanol. In another study, 61 these authors investigated the concentration of CTABr after ultrasonic irradiation using a doublebeam UV spectrophotometer. As shown in Figure 7(d), the concentration of CTABr was increased by increasing the sonication time; however, further increasing sonication time resulted in a decrease of CTABr concentration indicating that degradation of CTABr happened at longer sonication times.…”
Section: Template Removal Approachesmentioning
confidence: 99%
“…This method has been utilized for template elimination from the pores of mesoporous materials. The ultrasonic treatment was used for detemplating MCM-41 by Jabariyan and Zanjanchi , for the first time and later by Pirez et al for template removal from SBA-15 and propylsulfonic acid (PrSO 3 H)-functionalized SBA-15.…”
Section: Template Removal Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, an extraction in acidic ethanol solution produces thermally more stable mesoporous silica. Jabariyan and Zanjanchi [17] attempted to enhance the extraction process using methanol as a solvent in the presence of ultrasonic waves. The results indicated that the rate of template removal using the sonication method was very fast (15 min), and the majority of CTAB had been removed from powder MCM-41.…”
Section: Introductionmentioning
confidence: 99%